Digital, analogue, or redundant speedometers for truck driving: Impact on visual distraction, efficiency and usability. (November 2017) - François, Mathilde; Crave, Philippe; Osiurak, François; Fort, Alexandra; Navarro, Jordan
Abstract: Existing literature does not draw conclusions as to which speedometer type is better for truck driving. A digital speedometer would be more beneficial when obtaining absolute and relative readings, while an analogue speedometer would be more efficient and less distracting when detecting dynamic speed changes. Redundant speedometers, which simultaneously present digital and analogue speedometers, appear increasingly in vehicles, but no information is available on their ergonomic qualities. This study compared three speedometers: digital speedometers, analogue speedometers, and redundant speedometers. This study compared the efficiency, usability and visual distraction measures for all three types of speedometers in a simulated truck driving setting. The task-dependant results were confirmed for the digital and analogue speedometer. The redundant speedometer combined the benefits of each type presented separately, which highlights interesting theoretical and applied implications. Highlights: Digital and redundant speedometer are best to report a speed value. Digital and redundant speedometer are best to compare the speed to a target. Analogue and redundant speedometer are best to detect a dynamic speed change. Differences between speedometers were reduced when using speed management systems. Truck drivers prefer redundant speedometers.